Varietal Change Dominates Adoption of Technology in Spanish Citrus Production - De-Miguel, María D.; Caballero, Pedro; Fernández-Zamudio, María A. (2020)
After describing the technology adopted and its influence on production and yield, the importance of varietal change, which is essential to meet demand, is underscored. The choice of a variety by growers depends on the expected price it will fetch along with the commercial and crop characteristics and the quality. Survival of a variety in the marketplace depends on the performance as expected and on the existence of other more competitive varieties. First, in Spanish citrus farming, the navel group predominate, with 41.10% of orange production, in which the main varieties are "Navelina" and "Lanelate." The group of late white oranges is also important. The mandarin orange group includes clementines and mandarin hybrids; lemons also feature prominently. In sweet oranges, the navel group and late white group has often been renewed with varieties from the same group. In very early clementines varieties, the survival of which is usually short, the supply of new varieties is excessive. Because of its commercial characteristics and harvesting time, the group with the highest expansion possibilities are the mandarin hybrids which are in demand by hypermarkets. In the introduction of varieties, in recent years we have seen varietal clubs being established, with area control of each variety and very strict rules on cultivation and marketing.